Development of a Novel Emergency Department Mapping Tool. (January 2020) - Grzywinski, Matthew; Carlisle, Stephanie; Coleman, James; Cook, Connor; Hayden, Geoffrey; Pugliese, Robert; Faircloth, Billie; Ku, Bon
Objectives: Develop a built environment mapping workflow. Implement the workflow in the emergency department (ED). Demonstrate the actionable representations of the data that can be collected using this workflow. Background: The design of the healthcare built environment impacts the delivery of patient care and operational efficiency. Studying this environment presents a series of challenges due to the limitations associated with existing technology such as radio-frequency identification. The authors designed a customized mapping workflow to collect high-resolution spatial, temporal, and activity data to improve healthcare environments, with emphasis on patient safety and operational efficiency. Method: A large, urban, academic medical center ED collaborated with an architecture firm to create a data collection, and mapping workflow using ArcGIS tools and data collectors. The authors developed tools to collect data on the entire ED, as well as individual patients, physicians, and nurses. Advanced visual representations were created from the master data set. Results: In 48 consecutive hourly snapshots, 5, 113 data points were collected on patients, physicians, nurses, and other staff reflecting the operations of the ED. Separately, 84 patients, 10 attending physicians, 10 resident physicians, and 17 nurses were tracked. Conclusions: The data obtained from this pilot study were used to create advanced visual representations of the ED environment. This cost-effective ED mapping workflow may be applied to other healthcare settings. Further investigation to evaluate the benefits of this high-resolution data is required.